(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
When it comes to drawing 3D shapes, we do not get any easier than the Google Sketch Up program. The most important part of 3D drawing, especially in the field of architecture, is the ease of using the program, the ability to turn the idea into virtual reality, the Google sketch program Up, provides a user-friendly service that is not required for a powerful computer, and we all know that AutoCAD is one of the most powerful 3D drawing programs (if not the most powerful) but the difficulty of using it and the time it takes to learn has led most engineers to resort to the easiest program. indispensable but Google sketch programs gave up solutions faster and many choices in final directing. The study examined the problem of the use of the AutoCAD program and the suffering of the drawing teachers in understanding and using it. In contrast, it showed the advantages of the program, and compared it to the AutoCAD program, and presented a questionnaire by the researcher on a sample of the teachers of the engineering drawing in the degrading schools. program AutoCAD, and therefore, this program does not result in the expected purpose of it, so it became necessary to find an alternative at least to use it as a display of sculptures by engineering drawing teacher, and this alternative is a program Cockle Google sketch up.